Nutcracker syndrome in children: review of symptom, diagnosis, and treatment - Diana S. Kalantar; Se Jin Park; Jae Il Shin (Korean Society of Pediatric Nephrology, 2023)
Renal nutcracker syndrome (NCS) is the entrapment of the left renal vein between the abdominal aorta and superior mesenteric artery. Although uncommon in pediatric patients, early diagnosis is crucial to avoid potential severe complications, such as anemia or renal vein thrombosis. NCS presents a variety of symptoms, most commonly including "Triade's symptoms"-hematuria, proteinuria, and flank pain. Diagnosis and treatment include invasive and noninvasive management, although due to a lack of pediatric clinical studies, management is widely variable. Conservative diagnosis and treatment are recommended as a first-line option for pediatric patients; however, invasive surgical treatment may be recommended based on symptom severity. This review aims to provide a comprehensive overview of NCS in children to better understand the widely variable incidence, occurrence, and management from early on to allow for early-onset management.